PROSPECTIVE PRIMARY SCHOOL TEACHERS’ ACTIVITIES WHEN DEALING WITH MATHEMATICS MODELLING TASKS - Floriano Viseu; Paula Mendes Martins; Laurinda Leite (Journal on Mathematics Education, 2020)
The current teaching of mathematics is guided by recommendations that suggest the implementation of various activities in order to raise the understanding of mathematical knowledge. This diversity is related to the characteristics of the tasks proposed in the learning contexts. Among all tasks, the modelling ones call for the application of activities through different representations. So, it is important that teacher training courses promote experiences involving prospective teachers with this type of task. Based on this assumption, we intend to identify the activities that prospective primary school teachers perform in solving modelling tasks, the difficulties experienced in these tasks and the value of the models they determine. From the analysis of the resolutions of two tasks, we find that the prospective teachers translate the information of the data available in tables through graphs and analytical expressions. Some discuss models that determine which best fits the data. In the activities carried out, difficulties arise in determining the proportionality constant that best translates the problem situation, discussing the reasonableness of the values generated by the model, and sketching the graph of the model that best fits the experimental data. As for the usefulness of the model they determine, few prospective teachers are predicting outcomes.